Inverse Association between Occupational Ultraviolet Radiation and Renal Cell Carcinoma Incidence: A Systematic Review and Meta-Analysis - Rezza Dwi Haryanto (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2026)
Introduction: Renal cell carcinoma (RCC) incidence is rising globally. While lifestyle risk factors like obesity and smoking are established, environmental modifiers remain contested. Ultraviolet (UV) radiation induces endogenous vitamin D synthesis, which exhibits potent antineoplastic properties in renal tissues. This systematic review and meta-analysis investigated the association between occupational UV radiation exposure and RCC incidence, addressing confounding variables and geographic variations. Methods: Following PRISMA guidelines, a comprehensive search of PubMed, EMBASE, Cochrane Library, and Web of Science was conducted for observational studies published up to August 2024. Data extraction focused on occupational UV exposure and RCC incidence. Methodological quality was assessed using the Newcastle-Ottawa Scale. Meta-analysis utilized RevMan software to calculate pooled odds ratios (OR) and Standardized Mean Differences (SMD) with 95% confidence intervals (CI). Publication bias was evaluated via funnel plots and Egger’s test. Results: Ten high-quality studies encompassing 364,959 participants were included. The pooled meta-analysis demonstrated a statistically significant inverse association between occupational UV radiation and RCC incidence (OR 0.89; 95% CI 0.87–0.91; p < 0.00001) using a fixed-effects model. SMD analysis of cumulative exposure supported these findings. Subgroup analyses by gender indicated protective trends for both males (OR 0.80) and females (OR 0.75). Funnel plot symmetry indicated no significant publication bias. Conclusion: Long-term occupational UV radiation exposure is significantly associated with a reduced risk of RCC. This protective effect is likely mediated by sustained vitamin D synthesis modulating the renal tumor microenvironment. Future research must utilize personal dosimeters and account for latitudinal gradients to refine occupational health guidelines.